2007
DOI: 10.1111/j.1365-2133.2006.07602.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe psoriasis treated with a new macrolide: everolimus

Abstract: Psoriasis is an immune-mediated disease with a chronic relapsing course, and the particularly severe forms that are refractory to traditional therapies are often difficult to manage. Everolimus (Certican; Novartis, Basel, Switzerland) is a new rapamycin-derived macrolide that is used in the prophylaxis of rejection in heart and kidney transplant patients. The mechanism underlying its immunosuppressant and antiproliferative activity is different from, but complementary to, that of calcineurin inhibitors such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 12 publications
(13 reference statements)
2
24
0
Order By: Relevance
“…Clinical trials indicated that rapamycin, the prototypical mTOR inhibitor could significantly reduce the clinical score of psoriasis when treating psoriasis patients (Ormerod et al, 2005;Reitamo et al, 2001). Everolimus, a semisynthetic macrolide and a member of the mTOR inhibitors family, could lead to the resolution of recalcitrant psoriatic manifestations (Frigerio et al, 2007;Wei & Lai, 2015). Our results show that metformin significantly inhibited the phosphorylation of mTOR and its downstream gene p70S6K, indicating that metformin may also contribute to the inhibition of keratinocyte proliferation and inflammation.…”
Section: Discussionmentioning
confidence: 50%
“…Clinical trials indicated that rapamycin, the prototypical mTOR inhibitor could significantly reduce the clinical score of psoriasis when treating psoriasis patients (Ormerod et al, 2005;Reitamo et al, 2001). Everolimus, a semisynthetic macrolide and a member of the mTOR inhibitors family, could lead to the resolution of recalcitrant psoriatic manifestations (Frigerio et al, 2007;Wei & Lai, 2015). Our results show that metformin significantly inhibited the phosphorylation of mTOR and its downstream gene p70S6K, indicating that metformin may also contribute to the inhibition of keratinocyte proliferation and inflammation.…”
Section: Discussionmentioning
confidence: 50%
“…Remarkably, systemic rapamycin or its derivatives have been used for its immunosuppresive properties in anti-psoriatic trials alone or in combination with sub-therapeutic doses of cyclosporine and showed promising success [3941]. However, our data support the notion that psoriasis patients could rather benefit from the topical use of mTOR inhibitors on the affected skin, which showed encouraging results in a small trial [42].…”
Section: Discussionmentioning
confidence: 64%
“…Serious adverse reactions are noninfectious pneumonitis, infections with opportunistic pathogens, and oral ulcerations. Frigerio et al 154 reported a case of a woman with treatment resistant, chronic, relapsing psoriasis that was treated with a combination of everolimus 1.5 mg twice daily and cyclosporine (50 mg daily). The patient had significant improvement, but treatment was discontinued because the patient developed leukopenia by the fifth week.…”
Section: Everolimusmentioning
confidence: 98%